China's first Tourism Law: representations of stakeholders' responses. Issue 3 (27th May 2018) - Wang, Wan-Fei; Chang, Yao; Pearce, Philip L.
ABSTRACT: The application of tourism laws to advance the well-being of stakeholders is of broad interest to many countries attempting to shape the rapid rise of the sector. In China, the first Tourism Law came into effect on 1 October 2013. The 112-article law includes various measures to address issues such as unfair competition. Adopting a social representations framework, this study investigates the perceived impacts of China's new Law from the perspectives of eight groups of stakeholders. Data were collected from 152 articles published in the Chinese National Knowledge Infrastructure. This material was used to access the commentaries and social representations of the impacts of the Law. A consistent array of positive and negative comments was uncovered using content analysis, justifying a view that a hegemonic representation exists across the groups. Additionally, and somewhat unexpectedly, it was discovered that the new Law is also a catalyst for further conflicts requiring additional management. Pursuing a social representations framework as a way of integrating stakeholder views was seen to be valuable for future studies in China and elsewhere.